Representation of globalization on Youtube video “Wonderland Indonesia” - adinda putri, Adinda Putri Surya Kencana; filosa gita, Filosa Gita Sukmono (COMMICAST, 2022)
Globalization occurs in tandem with the development of technology to become more sophisticated. The development of globalization can have an impact on every line of people's lives, one of which is culture, so that its spread can also be through the internet, one of which is through YouTube videos. This study aims to see how globalization is represented by Alffy Rev through his work entitled "Wonderland Indonesia". John Fiske's semiotic method with the theory of The codes of television is used to examine how globalization is characterized through the music video. The results show that the representation of globalization that is presented tends to describe the diversity of Indonesian culture that is packaged in a modern way through the signs displayed, such as illustrations and there are several scenes with the background of traditional houses, traditional clothes used, and the music used is a combination of several songs. areas that have been combined with elements of EDM music.